Factors That Can Influence the Tendency of Accounting Fraud - Meliawati, Resna; Saepudin, Didin (Maksi, 2023)
The tendency of accounting fraud is influenced by several factorssuch as individual moral behavior, the effectiveness of internal control and the appropriateness of compensation in Cimahi City SMEs are the objectives of this study. Primary data was collected using a saturated sample or non-probability sampling method from a questionnaire. The population of this study is Cimahi city MSME employees who have penetrated the global market, totaling 148 employees. While the samples taken were 50 respondents. The instrument test for the questionnaire statements includes validity and reliability tests to then test the normality of the data up to the hypothesis test. Methods of data analysis using multiple linear regression techniques. Simultaneously individual morality, the effectiveness of internal controls and the suitability of compensation affect the tendency of accounting fraud which is the result of the research obtained.